Major challenges facing small and medium-sized enterprises in Asia and solutions for mitigating them - Naoyuki Yoshino; Farhad Taghizadeh-Hesary (Asian Development Bank Institute (ADBI), 2016)
Small and medium-sized enterprises (SMEs) are the backbone of the Asian economy. They make up more than 98% of all Asian businesses that provide two out of three private sector jobs in the region. Therefore, it is vitally important for Asia's economic success to have fully functioning support measures for SMEs. However, SMEs face challenges from limited access to finance, lack of databases, low R&D expenditures, undeveloped sales channels, and low levels of financial inclusion, which are some of the reasons behind the slow growth of SMEs. This paper focuses on four major reasons that slowed the SME growth in Asia including i) lack of finance, ii) lack of comprehensive databases, iii) low level of R&D expenditures, and iv) insufficient use of information technology and provides remedies for mitigating them.
Keywords: G21; G24; G32; 330; SME databases; financial inclusion; SME investment; R&D expenditure